Student challenges and successes in integration of planetary health in medical education: a mixed methods analysis - Kanika Malani; Emily Yamron; Kate Tokareva; Taylor Brewer; Alexander Northrop; Lauren Franklin; Kyle Denison Martin (Frontiers in Public Health)
IntroductionThis study evaluates challenges and successes faced by medical students leading planetary health (PH) curriculum reform and tracks changes over time.MethodsThe Planetary Health Report Card (PHRC) is a standardized, metric-based tool for assessing PH education in medical schools. In October 2023, a survey was emailed to 132 medical students across 52 US institutions who had served as primary contacts for their school’s most recent PHRC between 2020 and 2023. The survey explored challenges and successes in integrating PH into the curriculum. A total of 31 students from 17 US states responded. All respondents were invited to follow-up Zoom interviews, with 11 completing them. Survey and interview data were analyzed using descriptive statistics and directed content analysis, while longitudinal PHRC data were assessed using Wilcoxon signed-rank tests.ResultsStudents are primary stakeholders in PH integration (N = 28, 90%). While other stakeholders were perceived as generally supportive, surveyed students felt these groups were less likely to lead PH curricular reform and may lack confidence in delivering PH content (N = 7, 70.0%). Interviewees (N = 11) noted various obstacles and suggested potential solutions to improve PH integration into medical curricula.DiscussionMedical schools should prioritize developing longitudinal, course-specific PH education, supported by both individual institutions and national frameworks and licensing organizations.